Idiopathic hypertrophic pachymeningitis - K, Abhilash; KL, Minimol (International Journal of Research in Medical Sciences, 2017)
Idiopathic hypertrophic pachymeningitis is a rare form of granulomatous meningitis. It is mainly a diagnosis by exclusion. Here we are presenting a case of a young female presented with multiple cranial nerve palsies who was diagnosed to have hypertrophic pachymeningitis with the help of MRI brain. All available investigations showed negative results and so possibility of Idiopathic Hypertrophic Pachymeningitis was considered. The patient responded well to steroid therapy.